Penerapan Employee Satisfaction Untuk Mengetahui Kepuasan Karyawan PT XYZ - Vanessa Caesarika, Mechtildis; Dwi Sukma Donoriyanto (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
PT XYZ is a company providing superior international logistics services which specifically focuses on handling customs and international shipping. With a high dedication to operational excellence and unmatched customer service, PT XYZ has built a solid reputation as a trusted partner in facilitating and expediting the global supply chain for various customers in various industrial sectors. Employee satisfaction is not just numbers or data. But it also relates to how employees feel they are treated by their superiors and the company as a whole. Employee satisfaction PT XYZ can create a work environment that motivates employees to perform high and work together in achieving company goals. Writing this report aims to analyze the factors that influence employee satisfaction which can be a key factor in achieving this goal. This activity was carried out using a survey with a questionnaire using 6 aspects of employee satisfaction and obtained an ESS score of 3.93, this figure is relatively high when compared with the score ESS in Indonesia (3.75) however has decreased compared to the ESS figure in 2022 (3.95).